Tax exemptions and their role in improving sustainable environmental performance in companies- An applied study in the General Tax Authority - Anwar Hashem Abboud (Scholar Express Journals, 2024)
Many countries have used tax exemptions as a method to implement their policies, either to encourage certain behavior or to limit another behavior, and to successfully implement the exemption and achieve its feasibility on the one hand, and to reduce environmental pollution caused by companies and to reduce environmental pollution instead of penalties, fines, and environmental taxes, tax exemptions can be used for the purpose Environmental protection ,and its role in improving the environmental behavior of companies. From here the research problem emerged regarding the ineffectiveness of fines and environmental taxes, as companies bear the payment of fines that are not matched by an improvement in environmental performance, and thus the volume of environmental pollution increases. The research aimed to identify tax exemptions and their types, as well as explain the concept of sustainable environmental performance, and demonstrate the importance of tax exemptions in improving the sustainable environmental performance of companies. The most important conclusions that were reached through analyzing the answers of members of the research sample. We noted their support for the necessity of amending tax laws to include granting tax exemptions to reduce and reduce environmental pollution and the role of these exemptions in encouraging companies to improve their environmental performance and its reflection at the company level in multiple aspects. The most important recommendations were that it was necessary to grant tax exemption for environmental purposes because of its major role in improving the sustainable environmental performance of companies, since tax exemption is the most important type of tax incentives granted by the state
Keywords: tax exemptions; environmental performance; types of environmental tax exemptions